Bioimprint aided cell recognition and depletion of human leukemic HL60 cells from peripheral blood. Issue 22 (7th May 2019) - Das, Anupam A.K.; Medlock, Jevan; Liang, He; Nees, Dieter; Allsup, David J.; Madden, Leigh A.; Paunov, Vesselin N.
Abstract : We report a large scale preparation of bioimprints of layers of cultured leukemic HL60 cells which can perform cell shape and size recognition from a mixture with peripheral blood mononuclear cells (PBMCs). Abstract : We report a large scale preparation of bioimprints of layers of cultured human leukemic HL60 cells which can perform cell shape and size recognition from a mixture with peripheral blood mononuclear cells (PBMCs). We demonstrate that the bioimprint-cell attraction combined with surface modification and flow rate control allows depletion of the HL60 cells from peripheral blood which can be used for development of alternative therapies of acute myeloid leukaemia (AML).